Pengujian Sistem ERP Apotek (GPOS - POS Modul) Menggunakan Metode Black Box dengan Teknik Error Guessing - Yulianti Yulianti; Endar Nirmala; Eva Fauziah; Rizky Chaesar; Muhammad Rafif Misbahuddin; Fernando David Hence Rotty (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
After the process of making software needs to be done a useful testing stage to ensure that the software (Software) is in accordance with the needs of the user. POS is an application used to make sales transactions. In this study, the test was conducted on four modules: the first is the inventory module, in this module there are features for the manager of goods data, stock of goods, and the price of goods, The second is the purchase module where this feature will manage every transaction of goods purchased to the supplier or manufacturer, the third is the sales module or POS, this feature is designed to manage every sales transaction to the customer or end user, and the last is the report module, where every transaction both sales and purchases and inventory data (items, stock,  the price) will be recorded in detail in it. Each of these modules is arranged thus completing one cycle of business processes. Because of the complexity of the arrangement of logic forming sales transactions, the process of calculating the price of sales and calculating the value of stock goods causes losses for business people who use invalid systems. As for a case in true testing it's when we find a previously undisclosed error. The research phase begins by analyzing each function on the system to be tested, creating a testing scenario for the database structure that has been created, making documentation from the test results and the researcher concludes. From the results of the tests that have been done, it was concluded that this software is worth using.